UJI SIFAT ELEKTRONIK FILM Bax Sr1-xTiO3 DENGAN METODE WERNER - Endang Rancasa (Jurnal Biofisika, 2013)
In  this  study,  BaxSr1-xTiO3(BST)  films  were  grown  on  p-silicon  substrates  using chemical solution deposition (CSD) and were annealed at 850oC for 15 hours.  Then contact were made on its. Measurement of electrical properties has been observed using sourcemeter and then its were analyzed using werner method to extract seriesresistance and  ideality factor.  Then  value  of series  resistance  w as used  to  correct voltage data Vd. Then graphs of Vd – Ln I were analyzed to extract saturation current, barrier  potential  and  ideality  factor.  The  increasing  of  mol  fraction  of  Ba  caused increasing in saturation current and reduces value of series resistance, ideality factor and barrier potential.